Association Between Time‐in‐Therapeutic Tacrolimus Range and Early Rejection After Heart Transplant. Issue 5 (2nd April 2019) - Baker, William L.; Steiger, Samantha; Martin, Spencer; Patel, Nirav; Radojevic, Joseph; Darsaklis, Konstadina; O'Bara, Lynn; Kutzler, Heather; Dougherty, James; Feingold, Andrew; Hammond, Jonathan; Fusco, Daniel; et al.
Abstract : Background: Historically, there is perceived pressure to achieve therapeutic levels of tacrolimus quickly after heart transplant (HT). We evaluated the association between time within therapeutic tacrolimus range and time to therapeutic trough and rejection in the 30 days following HT. Methods: This is a single‐center retrospective cohort study of consecutive adult HT patients receiving immunosuppression. Goal trough tacrolimus levels were 10–15 ng/ml. Surveillance endomyocardial biopsies were performed weekly for 4 weeks. Outcomes included the effect of time to and time‐in‐therapeutic tacrolimus range (Rosendaal method) on 30‐day clinical rejection, 1R/1B, and 2R or higher histologic occurrences. Results: We reviewed 67 HT patients (median age 58.8 yrs). For clinical rejection versus no‐rejection groups, the median (25th, 75th percentile) time to therapeutic tacrolimus levels was 9.5 (8, 12.3) days versus 9.0 (7, 13) days (p=0.623). The median time‐in‐therapeutic tacrolimus range was 34.1% (23.2, 42.2) versus 36.2% (19.9, 51.2), respectively (p=0.512). Similarly, we observed no significant differences in time to and time‐in‐therapeutic tacrolimus range in patients who developed grade 1R/1B (p=0.650 and p=0.725) or grade 2R or higher histology (p=0.632 and p=0.933). Conclusions: Our small single‐center analysis suggests that neither time to nor time in therapeutic tacrolimus range predicted acute rejection within 30 days of HT.